(untitled) (TAMADDUN NURI JURNALI, 2025)
This article is devoted to the study of the ethical and aesthetic aspects of Islamic architecture in the southeastern regions of Bukhara Emirate. Islamic architectural monuments are interpreted not only as religious centers, but also as an expression of moral values and cultural heritage.